Titanium Alloy Repair with Wire-Feed Electron Beam Additive Manufacturing Technology - P. Wanjara; K. Watanabe; C. de Formanoir; Q. Yang; C. Bescond; S. Godet; M. Brochu; K. Nezaki; J. Gholipour; P. Patnaik (Advances in Materials Science and Engineering)
Wire feeding can be combined with different heat sources, for example, arc, laser, and electron beam, to enable additive manufacturing and repair of metallic materials. In the case of titanium alloys, the vacuum operational environment of electron beam systems prevents atmospheric contamination during high-temperature processing and ensures high performance and reliability of additively manufactured or repaired components. In the present work, the feasibility of developing a repair process that emulates refurbishing an “extensively eroded” fan blade leading edge using wire-feed electron beam additive manufacturing technology was examined. The integrity of the Ti6Al4V wall structure deposited on a 3 mm thick Ti6Al4V substrate was verified using X-ray microcomputed tomography with a three-dimensional reconstruction. To understand the geometrical distortion in the substrate, three-dimensional displacement mapping with digital image correlation was undertaken after refurbishment and postdeposition stress relief heat treatment. Other characteristics of the repair were examined by assessing the macro- and microstructure, residual stresses, microhardness, tensile and fatigue properties, and static and dynamic failure mechanisms.